Antibodies and Vaccines Target RBD of SARS-CoV-2 - Min, Long; Sun, Qiu (Frontiers in Molecular Biosciences, 2021)
The novel human coronavirus SARS-CoV-2 which gives rise to Coronavirus disease 2019 (COVID-19) has caused a serious threat to global public health. On 11 March 2020, World Health Organization has officially announced COVID-19 as a pandemic. Therefore, it is vital to find effective and safe neutralizing antibodies and vaccines for COVID-19. The critical neutralizing domain (CND) that is contained in the RBD of spike protein could lead to highly potent neutralizing antibody response as well as cross-protection of the other strains of SARS. By using the RBD as an antigen, many neutralizing antibodies are isolated that are essential to the therapeutics of COVID-19. Furthermore, a subunit vaccine which is based on the receptor-binding domain (RBD) is expected to be safer than others, thus the RBD in the S protein is a more important target for vaccine development. In this review, we focus on the neutralizing antibodies targeting the RBD as well as the vaccine based on the RBD under current development.